Non-uniqueness and prescribed energy for the continuity equation - Crippa, Gianluca; Gusev, Nikolay; Spirito, Stefano; Wiedemann, Emil (Communications in Mathematical Sciences, 2015)
In this note, we provide new non-uniqueness examples for the continuity equation by constructing infinitely many weak solutions with prescribed energy.
CRIS-Team Scopus Importer:2023-01-17
Keywords: Convex integration; Non-conservation of energy; Non-uniqueness; Renormalization; Transport and continuity equations